MeV range particle physics studies in tokamak plasmas using gamma-ray spectroscopy. (8th November 2019) - Nocente, M; Molin, A Dal; Eidietis, N; Giacomelli, L; Gorini, G; Kazakov, Y; Khilkevitch, E; Kiptily, V; Iliasova, M; Lvovskiy, A; Mantsinen, M; Mariani, A; et al.
Abstract: Gamma-ray spectroscopy (GRS) has become an established technique to determine properties of the distribution function of the energetic particles in the MeV range, which are fast ions from heating and fusion reactions or runaway electrons born in disruptions. In this paper we present a selection of recent results where GRS is key to investigate the physics of MeV range particles. These range from radio-frequency heating experiments, where theoretical models can be tested with an unprecedented degree of accuracy, to disruption mitigation studies, where GRS sheds light on the effect of the actuators on the runaway electron velocity space. We further discuss the unique observational capabilities offered by the technique in deuterium–tritium plasmas, particularly with regard to the inference of the energy- and pitch-resolved distribution function of the α particles born from fusion reactions in the plasma core.